Population analysis of demersal and deep water chondrichthyes (Vertebrata: Chondrichthyes) along the Caribbean coast of Central America based on a fishery survey using bottom trawling - Benavides M, Rosario (2014)
The abundance, richness, diversity, and distribution are described for deep water chondrichthyan fauna collected during a survey of Oceanographic Vessel Miguel Oliver along the continental shelf on the Caribbean coast of Central America from January 3rd to February 3rd, 2011. A Lofoten net was used for bottom trawling for 30 minutes, in each of 96 different sampling points distributed along 25 equidistant transects. A total of 28 species was collected belonging to six orders and ten families. In addition, 8 species of rays, 5 species of chimaeras and 15 species of sharks are described.  The Squalidae family showed the highest abundance (n = 184), richness (7 species) and biomass (222.6kg, 58%). The dominant species was S. cubensis represented by 37% collected. The highest Shannon Diversity Index was obtained along the Nicaraguan coasts (2.051). The distribution of species by temperature and depth was between 4 and 16ºC and between 20 and 1,000 m. In addition, eight species were reported for the first time for this area H. mirabilis, R. atlantica, D. profundorum, C. tesselatus, E. gracilispinis, E. carteri, G. springeri and H. perlo.